(untitled) (Indian Journal of Animal Production and Management, 2015)
A study on management practices and economics of broiler farming was conducted in two districts of Assam, viz. Lakhimpur and Sonitpur. The data were collected from 100 numbers of respondents by a pre-tested interview schedule. The result showed that majority of the respondents in both districts reared broilers on semi-pucca (low cost poultry house constructed with locally available materials having cemented floor) house on deep litter system did not maintain proper farm records. Feed was the major operating cost in both the district. The cost of production and income per batch of broiler was significantly (P d” 0.01) higher in Sonitpur as compared to Lakhimpur district, which might be due to the higher flock size of broilers in Sonitpur as compared to Lakhimpur. However, the income per broiler was non-significant (Pe”0.05). It could be concluded that broiler farming in Sonitpur district is better in terms of farm infrastructure and flock size leading to higher returns in comparison to Lakhimpur district.